2018
DOI: 10.1177/0363546518773757
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Psychological Readiness to Return to Sport After Anterior Cruciate Ligament Reconstruction Surgery

Abstract: Self-reported symptoms and function were most associated with psychological readiness to RTS after ACLR surgery. Male patients who participated frequently in sport before ACL injury had higher psychological readiness. Conversely, female patients had a more negative outlook and may therefore benefit more from interventions designed to facilitate a smooth transition back to sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(196 citation statements)
references
References 36 publications
(57 reference statements)
9
173
1
1
Order By: Relevance
“…Also, psychological aspects are not taken into account. Recent studies have shown an influence of psychological parameters on performance and progress for return to sport [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Also, psychological aspects are not taken into account. Recent studies have shown an influence of psychological parameters on performance and progress for return to sport [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a psychometrically robust outcome measure of perceived knee function is crucial for clinicians and researchers alike. A patient's perceived knee function is associated with a number of recovery outcomes, including a fear of re-injury, 9 and a readiness to return to sport, 10 both of which have been identified as risk factors in failing to return to sport 4 and sustaining a second ACL injury upon return. 11 Furthermore, failing to return to sport and subsequent injury have been shown to detrimentally affect patients' long-term quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological readiness for return-to-sport (a common goal of ACLR), and fear of reinjury was measured by the ACL Return to Sport Index (ACL-RSI) (68). The ACL-RSI is valid, reliable and responsive to change (MIC = 19 points)(40), with higher scores associated with better self-reported symptoms and function (69). The global rating of change (GROC) on a 7-point Likert scale ("much worse" to "much better") measured separately for knee pain and knee function; and the change in proportion of patients answering "yes" to the patient acceptable symptom state (PASS) question (35) were evaluated.…”
Section: Secondary Subjective Outcomesmentioning
confidence: 99%